British Thoracic Society Quality Standard for Clinically Significant Bronchiectasis in Adults 2022. Issue 1 (5th October 2022) - Hill, Adam T; Grillo, Lizzie; Gruffydd-Jones, Kevin; Payne, Karen; Souto, Miguel; Sullivan, Anita; Wildgoose, James; Loebinger, Michael R
Abstract : This British Thoracic Society Quality Standard for Clinically Significant Bronchiectasis in Adults 2022 aims to encourage good practice by setting standards of high-quality respiratory care that services should follow.